Impact of Treatment with Imatinib on Renal Histology in Albino Rats - Al-Allaf, Luma; Al-Ashoo, Hafidh (Jordan Medical Journal, 2020)
Background: Targeted small molecule drugs have revolutionized treatment of chronic myelogenous leukemia(CML) over the last decade. however, their use has been found to be associated with serious toxic effects on a number of vital organs including the kidneys. Objectives: This study aims to determine the histological changes of the kidney of rats after administration of a dose of 75mg/kg/once/day of Imatinib mesylate for one month in comparison to control ones. Study setting and design: This experimental study was conducted on 16 male Albino rats purchased from Animal Houses of Veterinary College, University of Mosul, Mosul, Northern Iraq. Methods: In this study a group of eight rats (40- 45 days) were administered orally daily dose of 75mg/Kg/30 days of imatinib mesylate (Glivec®; Novartis). Another group of 8 rats (40- 45 days) were administered distilled water(D.W) . Kidneys tissues from each rat were obtained. The tissues were embedded in paraffin and stained with hematoxylin-eosin, periodic acid schiff +Hematoxylin stain, Toluidin blue, and Masson’s Trichrome. Results: Rats treated with 75mg/kg /once/day of imatinib for 30 days showed different histological changes in glomeruli and some parts of the urinary tubules in comparison with controls. The most evident features are increase in Bowman’s space, presence of lobulated or segmented glomeruli, shrunken glomeruli, dilated tubules with sloughed epithelium, and cloudy degeneration. Congested glomerular capillaries are also noticed sometimes in these sections with decreased Bowman’s space .Dramatic renal injury in these rats was represented with tubular cell swelling, loss of brush border of proximal convoluted tubules as well as presence of cloudy degeneration of tubules. In addition, there was a focal accumulation of inflammatory cells of early inflammation that infiltrate between the tubules at the cortical and corticomedullary portion and early fibrosis is noticed. Sections obtained from rats treated with imatinib exhibit dilatation and hyperemia in the intertubular cortical or juxtamedullary blood vessels with appearance of structureless esinophilic area of necrosis . In addition , dilated tubules with accumulation of eosinophilic homogenous material in tubular lumen were noticed . The interstitial tissue showed area of hypercellularity, interstitial oedema and infiltration of mononuclear inflammatory cells (lymphocytes) which tend to be concentrated around the tubules in the cortical and medullary zones. Conclusion: Imatinib has adverse effects on the renal histology and results in alterations in the renal cortex glomerular cells or tubular, which could play an important role in renal dysfunction. A clinical collaboration between oncologists and nephrologists could be useful with the objective to optimize the management of tyrosine kinase inhibitors.